Pemanfaatan Limbah Minyak Jelantah di Kelurahan Banjarsari Surakarta sebagai Lilin Aromaterapi - Ani Rakhmawati; Awanda Elrita Putri; Angelita Widyawati; Muhammad Aditya Wisnu Wardana (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Candles are a source of light energy that is solid and has a wick that is easy to burn. Along with the times, the function of candles can also be used as a room deodorizer or aromatherapy. Making candles by utilizing waste cooking oil is an effort to reduce household waste. Pandan leaves as aromatherapy can be found easily in the yard. Training on the process of making pandan leaf aromatherapy candles was carried out targeting members of the PKK RT 01, RW 08, Banjarsari Village. This training was given considering that most of the residents are MSME actors in snacks that use cooking oil. The results of the study show the enthusiasm of PKK members to learn and it is hoped that this will generate additional income from the MSME sector